Do trade and investment agreements lead to more FDI? Accounting for key provisions inside the black box - Axel Berger; Matthias Busse; Peter Nunnenkamp; Martin Roy (World Trade Organization (WTO), 2010)
The previous literature provides a highly ambiguous picture on the impact of trade and investment agreements on FDI. Most empirical studies ignore the actual content of BITs and RTAs, treating them as black boxes, despite the diversity of investment provisions constituting the essence of these agreements. We overcome this serious limitation by analyzing the impact of modalities on the admission of FDI and dispute settlement mechanisms in both RTAs and BITs on bilateral FDI flows between 1978 and 2004. We find that FDI reacts positively to RTAs only if they offer liberal admission rules. Dispute settlement provisions play a minor role. While RTAs without strong investment provisions may even discourage FDI, the reactions to BITs are less discriminate with foreign investors responding favourably to the mere existence of BITs.
Keywords: F21; F23; K33; 330; foreign direct investment; bilateral investment treaties; regional trade agreements; admission rules; investor-state dispute settlement; Direktinvestition; Investitionsgarantie; Handelsabkommen; Regionaler Außenhandel; Internationale Schiedsgerichtsbarkeit; Schätzung; Welt